Using a Blended Learning Approach in the Secondary Mathematics Classroom - Aronson, Ann (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Blended learning combines aspects from the traditional face-to-face setting and an online learning environment. This type of learning environment provides a variety of benefits to students that are not otherwise available in purely face-to-face classrooms or online learning environments. Secondary mathematics teachers can utilize a blended learning set-up that incorporates the characteristics that make up an effective classroom specifically by looking at the National Council of Teachers of Mathematics (NCTM) Mathematical Teaching Practices. There are many aspects of the blended learning environment that allow for these teaching practices to be incorporated into the classroom and even enhanced when compared to what the traditional classroom can offer.